Knowledge and attitude among Egyptian medical students regarding the role of human papillomavirus vaccine in prevention of oropharyngeal cancer: a questionnaire-based observational study - Mohammed. N. Abdelaziz; Abdullah Hefnawy; Hajer Azzam; Omar Reisha; Omar Hamdy (Scientific Reports)
Abstract Squamous cell carcinomas in several anatomical sites are caused by human papillomaviruses (HPV), and oncogenic double-stranded DNA viruses. There are about 200 genotypes; HPV16 is the most often occurring variant. Potential ways of infection are skin warts, sexual activity, exposure, immunization, or oral sex. The growing incidence of OPSCC in Western countries makes vaccination increasingly vital. The FDA has approved the 9-valent vaccination as an OPSCC prophylactic agent. Still, political will, inadequate financing, and inadequate infrastructure help to explain the slow dissemination of anti-HPV vaccination. This study sought to evaluate Egyptian medical students’ knowledge, awareness, and attitude toward the advantages of HPV vaccination to prevent HPV-associated OPC. The study was a cross-sectional questionnaire-based study consisting of 696 participants from the first to fifth-year students enrolled in any Egyptian medical school registered in the academic year 2023–2024, specifically from June to August 2024, except non-medical, graduate, and non-Egyptian students who met the exclusion criteria. We privately gathered answers via colleagues and electronically via online Google forms posted on social media groups. This study concentrated on the poor knowledge of HPV among Egyptian medical students, particularly urban male students with a mean age of 21.72 ± 1.6 enrolled in clinical years mostly in Cairo, Sharqia, and Gharbia governorates. There was a clear fair attitude regarding the HPV vaccination, especially among urban male students with a mean age of 21.64 ± 1.65 enrolled in clinical years mostly in Cairo, Sharqia, and Alex governorates. Notably, only 7.7% of the students enrolled in the study knew the link between HPV and OPC. However, only 28.5% of participants have received the vaccine. The students said that lack of awareness (82.4%) was the most important obstacle to vaccination; followed by cultural attitudes (44.5%), vaccine accessibility (42.7%), and vaccine cost (41.3%). Ultimately, it was found that Egyptian medical students—especially those enrolled in clinical years in the governorates of Cairo, Sharqia, and Gharbia—have a low degree of knowledge of HPV-related oropharyngeal cancer and its vaccination role. Although preclinical students’ knowledge had greatly improved, the limited awareness—especially among clinical students—was concerning.